Estudo da utilização de cinza da casca do arroz residual em concretos estruturais: uma análise da durabilidade aos cloretos - Pedrozo, Eder Claro (2008)
The use of residues, as the rice husk ash (RHA) in the concrete s production reduces the environmental impact caused in its productive chain. It means fewer energy s consumption, fewer natural resources waste, less environmental pollution and lower aggregated cost. In the present study, the viability of using residual RHA, in natura (non-ground) or ground, on structural concrete, in partial substitution to the Portland cement was investigated, starting from the durability chloride ions analysis. In such a way, five cementitious blends, two composed by natural RHA, two with crushed RHA and one as a reference sample were tested. The substitution s rates were 15% and 25%. The water/binder relations used were 0.45, 0.55 and 0.65. The samples were tested for chloride penetration according to ASTM C 1202 (Rapid Chloride Permeability Test) and for long-term test (colorimetric method). Additionally, the tests of axial compressive strength and water absorption by immersion, according to the ABNT prescriptions were conducted. The obtained results showed that is viable to use residual non-ground RHA as partial substitution to Portland cement in structural concretes. For the axial compressive strength at 91 days and to the same relation w/b, in general, the residual non-ground RHA blends showed higher performance than those presented by the reference mixture. In the RCPT the use of RHA resulted in decreases in the passing charges that, in general, promoted improvement in the mixtures ratings on the chloride penetrability, compared with the reference mixtures. In long-term test, the use of RHA burnt without temperature control, also promoted improvements in the mixture performances, compared to the reference mixtures, with reductions in the chloride penetration coefficients. But the mixtures were dissimilar when compared to those presented by the RCPT. In the case of water absorption by immersion, it was found that the use of RHA, in general, increased the concrete water absorption, however, the results presented by mixtures composed with RHA were close to those of reference ones.